A new species of the Madagascan genus Pseudorphnus (Coleoptera: Scarabaeidae: Orphninae) - Frolov, Andrey V. (Zootaxa, 2011)
Pseudorphnus carinatus new species is described from northern Madagascar (Antsiranana Province). Males of the new species differ from other species of the genus in having a long (about 8/10 the width of clypeus) transverse ridge near anterior margin of the clypeus.